Influence of Customer Intimacy Strategy on Organisations’ Competitiveness in Tier III Category of Commercial Banks in Kenya - Alfayo Odongo Wamburi; Lucy Kibe; Henry Yatich (Eastern African Journal of Humanities and Social Sciences)
This study investigates how customer intimacy strategies influence the competitiveness of tier-III commercial banks in Kenya. Utilising a pragmatic research philosophy, it employs a mixed-methods approach and a descriptive cross-sectional design. Data were collected from middle and senior management across 21 tier III commercial banks, with a sample size of 288 respondents determined using Yamane's formula. Proportionate stratified random sampling ensured representativeness based on management staff functions. Regression analysis revealed a strong positive correlation (R = 0.822) between the Customer Intimacy Strategy and Organisational Competitiveness, explaining 67.5% of the variability. ANOVA results were highly significant (F (1, 238) = 494.589, p < .001), indicating the superiority of the regression model. The strategy showed individual significance with a t-statistic of 22.239 (p < .001) and a standardised beta coefficient of 0.822. Despite limitations, such as the focus on Kenyan tier III banks and potential response bias, the study provides actionable insights for banking sector decision-makers, emphasising the importance of prioritising customer intimacy for sustainable competitive advantages.